Grassfields Stories from Cameroon - Vakunta, W.; Vakunta, W. (Langaa RPCIG, 2008)
Grassfields Stories from Cameroon is an anthology of short stories. It comprises animal trickster tales, bird survival tales, and human-interest stories. The compendium is a reflection of the mores, cultures, and value systems of the indigenous peoples of the Northwest Province of Cameroon. It is motivated by the author's keen interest in the preservation of Cameroonian oral traditions in written form. These stories deal with the day-to-day life of the sedentary and the globe-trotter. Each story is sufficient onto itself. The author has intentionally avoided chronology in the order of presentation of the stories. Whether you read the stories in the order in which they are presented or dart about as your fancy dictates, you will feel the abundance of richness and entertainment the book contains. The didactic value of this collection of short stories resides in its suitability to readers of all age groups. The uniqueness of the volume lies in its universal appeal. Peter Wuteh Vakunta was born and raised in the village of Bamunka-Ndop in Cameroon where he worked as senior translator at the Presidency of the Republic before immigrating to America. He is an alumnus of Sacred Heart College-Mankon. Vakunta obtained his Bachelor degrees in Cameroon and Nigeria; MA and MSE degrees in Cameroon and the U.S.A. At present, Vakunta and his family live in Madison, U.S.A. He teaches in the Department of French and Italian at the University of Wisconsin-Madison where he is also completing his PhD dissertation titled: Translation in Literature: Indigenization in the Francophone Text. Vakunta is poet, storyteller and essayist. His published works include Better English: Mind Your P's and Q's, Lion Man and Other Stories (short stories), Brainwaves (poems), Pandora's Box (poems). African Time and Pidgin Verses (poems), Square Pegs in Round Holes (essays) and It Takes Guts (essays). Vakunta's literary works have earned him several awards in the U.S.A, U.K and Africa.